Recent Referees (Journal of Political Economy, 2021)
Previous articleNext article FreeRecent RefereesPDFPDF PLUSFull Text Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinked InRedditEmailQR Code SectionsMoreJournal of Political Economy acknowledges the assistance of:Ran AbramitzkyDilip AbreuDaron AcemogluAlessandro AcquistiGeorge AlessandriaS. Nageeb AliTreb AllenOmar Al-UbaydliBjoern BartlingJeanet BentzenMartin BerajaJames BerryCarola BinderFrederic BoissayStéphane BonhommeMaristella BotticiniLaurent BoutonMarkus BrunnermeierEric BudishMike BurkartLuís CabralSteven CallanderDavide CantoniGabriel CarrollJuan CastilloFederica CoelliOlivier CoibionRiccardo ColacitoThomas CovertMariano M. CroceJosé CuestaDiego DaruichJoel DavidOlivier De GrooteJonathan de QuidtCary DeckAdeline DelavandeTatyana DeryuginaMichael DinersteinJonathan DingelUmut DurMatt ElliottRuben EnikolopovTeresa FortMarco FrancesconiAlexander FrankelChao FuJana GallusAshvin GandhiJared GarsCécile GaubertYuriy GorodnichenkoBryan GrahamCorbett GraingerJulien GrenetJeff GroggerAdam GurenGlenn HarrisonArshia HashemiJie HeJonathan HeathcoteNathan HendricksRichard HornbeckErik HovenkampJonathan HughesIngrid HuitfeldtJane HumphriesElisabeth IsaksenAsad IslamKoichiro ItoÒscar JordàCharles KahnPeter KaradiRyan KelloggJudd KesslerMichael KileyPéter KondorMiklós KorenBotond Ko˝ szegiJulian KozlowskiKory KroftPawel KrolikowskiHoward KungClauda LambertRasmus LandersøRobert LawsonMunseob LeeEric LeeperKenneth LeonardJacob LeshnoKai LiuJay LuJune MaEsfandiar MaasoumiAlexander MacKayYusufcan MasatliogluAdrien MatrayAlisdair McKayJonathan MeerLeonardo MelosiDaniel MillimetEduardo MoralesErica MyersSusanne NeckermannWojciech OlszewskiNuno PalmaNicola PavaniniChristopher PhelanDevesh RavalRicardo ReisMassimo RiccaboniClaudia Robles-GarciaKenneth RogoffRichard RomanoMarte RønningJuan Rubio-RamírezAldo RustichiniJames SalleeThomas SampsonFlorian ScheuerRaphael SchoenleBradley SetzlerJoseph ShapiroAlp SimsekDivya SinghKenneth SmallKerry SmithNicholas Snashall-WoodhamsChristopher SnyderJörg L. SpenkuchJon SteinssonJoerg StoyeJohannes StroebelDavid StrömbergMartin StuermerJan StuhlerSilvana TenreyroNicholas TrachterEgon TripodiMaxim TroshkinBertil TungoddenDaan van SoestDimitri VayanosXavier VivesMike WaughMichael WeberMatthew WeinzierlNathan WilsonChristian WolfHendrik WolffLiyan YangVincent YaoLawrence ZbikowskiYves ZenouOwen ZidarGabriel Zucman Previous articleNext article DetailsFiguresReferencesCited by Journal of Political Economy Volume 129, Number 9September 2021 Article DOIhttps://doi.org/10.1086/716773 Views: 581 © 2021 by The University of Chicago. All rights reserved.PDF download Crossref reports no articles citing this article.